Feasibility Analysis of Illustrated Concept Map-Based Handouts on Plant and Animal Organ System Material - Diana, Erna; Mulyadi (UNIVERSITAS PGRI MADIUN, 2024)
Teaching materials at MAS Al-Manar are limited to printed books, which hinders students' access to a variety of learning sources, particularly in abstract Biology topics. The research aimed to analyze the feasibility test of Handouts Based on Illustrated Concept Maps on Plant and Animal Organ System Material at MAS Al-Manar Aceh Besar. The research utilizes an Research and Development (R&D) model with a Borg and Gall research design. The research sample consisted of two media experts and two material experts. Data collection instruments include media feasibility test sheets and material feasibility test sheets. Analysis of feasibility data utilizes a percentage formula. The experts' media and material feasibility tests resulted in an average percentage of 83.5%, placing them in the highly feasible category. Based on the results of media and material feasibility tests, it can be concluded that the Handout is Based on Illustrated Concept Maps on Plant and Animal Organ System Material at MAS Al-Manar Aceh Besar.